Answer:
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b and c from the original equation and plug them into the quadratic formula.
3
2
+
6
+
1
8
=
0
3x^{2}+6x+18=0
3x2+6x+18=0
=
3
a={\color{#c92786}{3}}
a=3
=
6
b={\color{#e8710a}{6}}
b=6
=
1
8
c={\color{#129eaf}{18}}
c=18
=
−
6
±
6
2
−
4
⋅
3
⋅
1
8
√
2
⋅
3
x=\frac{-{\color{#e8710a}{6}} \pm \sqrt{{\color{#e8710a}{6}}^{2}-4 \cdot {\color{#c92786}{3}} \cdot {\color{#129eaf}{18}}}}{2 \cdot {\color{#c92786}{3}}}
x=2⋅3−6±62−4⋅3⋅18
2
Simplify